PROSEDUR IDENTIFIKASI ANAK KESULITAN BELAJAR YANG DIIMPLEMENTASIKAN OLEH GURUDI SDN INKLUSI - AGUNG SETIAWAN, GURUH (Jurnal Pendidikan Khusus, 2017)
Abstract. Early identification in school age was an important process to understand the potential and the necessity of special need children, included learning difficulty children. The earlier the process was done the more effective the developing effort of children’s potential was. Therefore, when the children were in elementary school level the identification should have been done exactly. Based on the information above, the focus of this research was to describe the identification procedure of learning diffculty children implemented by the teachers in Inclusion elementary school Sidoarjo regency. The purpose of this research was to describe the identification procedure of learning difficulty children applied by Inclusion elementary school in Sidoarjo regency. This research used qualitative kind of research with descriptive qualitative approach. The location for doing research was 10 Inclusion elementary schools in Sidoarjo regency. The data source of this research was the responsible agency of inclusion in each research location. The data collection techniques used in this research were interview and documentation. The test of data validation used was triangulation technique while the data analysis techniques used in this research were data reduction, data presentation, and verification. Based on the research result about the identification procedure of learning difficulty children implemented by the teachers in Inclusion elementary school in Sidoarjo regency, it could generally be concluded that the inclusion elementary school teachers in Sidoarjo regency applied various identification procedure of learning difficulty children but not all school which became the research location had fulfilled the identification procedure of learning diffculty children suitable with Kirt’s identification procedure i.e. S1 and S7.  Keywords: Identification procedure, learning difficulty children